Nostra aetate – stages of creation, with a particular focus on paragraph no. 2… and the people involved in its development - John Dupuche (Polonia Sacra)
Nostra aetate began as an important statement concerning the relations of the Church with the Jews but soon developed into a highly significant text on the relationship of the Church to all the religions of the world. While there been many works on the theology of Nostra aetate, there are few studies that present in detail the major personages and stages, the crucial issues and opposing forces surrounding this prophetic document. This article seeks to address this lacuna.